2002
DOI: 10.1111/j.0014-3820.2002.tb00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased Genetic Structure in the Vector of Lyme Disease, Ixodes Ricinus

Abstract: Abstract. We analyzed 725 Ixodes ricinus ticks (the principal vector of Lyme disease in Europe) collected in Switzerland in 1995 and 1996 (three and eight samples, respectively) and in Tunisia in 1996 (one sample) with five microsatellite markers. We found highly significant genetic differentiation between Swiss and Tunisian samples but detected almost no differentiation within Switzerland, even between those samples separated by the Alps. Interestingly, we found that I. ricinus females were more genetically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 53 publications
(44 reference statements)
1
18
1
Order By: Relevance
“…ricinus populations of continental Europe at both local and regional scales, but substantial differences between North African and European populations [9, 10, 19]. This discrepancy with our results may well reflect differences in sampling design, since the previous studies did not include the northwestern-most areas separated by open seas, as we did in our study.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…ricinus populations of continental Europe at both local and regional scales, but substantial differences between North African and European populations [9, 10, 19]. This discrepancy with our results may well reflect differences in sampling design, since the previous studies did not include the northwestern-most areas separated by open seas, as we did in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…ricinus . MtDNA is a particularly suitable marker for analyzing genetic structure in ticks due to both maternal inheritance and because long distance dispersal is more common for adult females than adult males [9, 28]. DNA from individual ticks was extracted using DNeasy TM Tissue Kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice of statistics is motivated by the work of Goudet et al [49] where v AI c was shown to be the most powerful statistic when migration is low (less than 10%), while F ST performs better in other circumstances. We also chose to keep m AI c because it may be more powerful in case of complex patterns of sex specific genetic structures [50], [51]. Tests were all bilateral.…”
Section: Methodsmentioning
confidence: 99%
“…This choice of statistics is motivated by the work of Goudet et al [37] where v AI c was shown to be the most powerful statistic when migration is low (less than 10%), while F ST performs better in other circumstances. We also chose to keep m AI c because it may be more powerful in case of complex patterns of sex specific genetic structures [39,40]. Tests were all bilateral.…”
Section: Methodsmentioning
confidence: 99%